PERANAN GADGET TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA 4-6 TAHUN DI PAUD BANI KARIM - Khulduniah; Umalihayati; Yolanda Pahrul (STKIP Subang, 2025)
This descriptive qualitative research focuses on an in-depth analysis of the influence of the use of gadgets on early childhood cognitive development in PAUD Bani Karim, considering that children in the Preoperational Stage (age 4-6 years) have the characteristics of imitating, observing, and being able to symbolize. The impact of dualistic gadgets can be positive or negative, which is highly determined by the way it is used and influenced by the diversity of individual factors of the child, such as interests, personality, social conditions, and intelligence levels. Using the case study method, this study aims to measure the significance of these impacts and explore the crucial role of educators and parents in guiding children. Data were collected through observation and direct interviews with principals, teachers, parents, and research subjects (group B1). The findings of the study show that the impact of gadgets has a great effect on cognitive development, depending on how the tool is operated. Therefore, synergy and collective support from the school and household environment are absolutely necessary to ensure that the use of gadgets can be an optimal means for improving children's cognitive development.